Varying uses of the ABCD2 scoring system in primary and secondary care: a qualitative study. Issue 6 (28th November 2012) - Edwards, Duncan; Cohn, Simon R; Mavaddat, Nahal; Virdee, Satnam K; Lasserson, Daniel; Milner, Siobhan; Giles, Matthew; McManus, Richard; Mant, Jonathan
Abstract : Objectives: To explore the usage of the ABCD2 risk stratification score by general practitioners (GPs) and hospital staff during the referral of patients with suspected transient ischaemic attack (TIA) or minor stroke. Design: Qualitative study using semistructured interviews. Setting: Nine general practices and two hospital sites in England (Birmingham and Cambridge). Participants: Nine GPs and nine hospital staff (two consultants, four nurses, two ultrasonographers and one administrator). Results: In both sites, clinicians used a referral proforma based around the ABCD2 scoring system for a range of purposes including self-education, to assist emphasising urgency to the patient, as a referral pathway facilitator and as a diagnostic tool. Negative views of its role included potential medicolegal threats, that it was a barrier to appropriate care, and led to misdiagnoses. Despite having differing uses by different clinicians, the ABCD2 proforma was the central means of interprofessional communication in TIA referrals across both sites. Conclusions: Understanding how prediction rules are used in practice is key to determining their impact on processes of care and clinical outcomes. In practice, GPs and their colleagues use the ABCD2 score in subtly different ways and it functions as a 'boundary object' by both accommodating these multiple purposes, yet still successfully aiding communication between them.